Design, construction and evaluation of a Fresnel Linear Concentrator for Oil Heating - Pedraza Yepes, Cristian Antonio; Higuera Cobos, Oscar Fabian; Hernández Vásquez, José Daniel; De La Hoz Muñoz, Nelson Jesús; Habib Naizir, Julio Gonzalez (Scientia et Technica, 2019)
The goal of this work is to describes the design and development of a fresnel linear concentrator that be able to concentrate sun radiations towards a receiver tube with a concentration ratio of 11, 54. The methodology applied allowed to analysis the spacing, the inclinations and the adequate widths of the mirrors that would be more convenient to obtain the highest solar concentration factor and the minimum optical and thermal losses. The design of the solar concentration collector consisted of a 3.5 m x 3.0 m x 2.65 m system with 15 mirrors, each one measuring 0.12 m wide, and a receiving center height of 2.0 m. The experimental results confirmed that the maximum process temperature of 140 ° C was achieved. In addition, a thermal oil storing was 995 kJ-h available in a 6-hour (since 9:00h until 15:00h). The performance tests of the system were performed in the city of Barranquilla, with local environmental conditions. The experimental tests of the prototype finally allowed to validate the design proposed in this present work.